Determinants of early antenatal care visits among women of reproductive age in Ghana: evidence from the recent Maternal Health Survey - Aaron Asibi Abuosi; Emmanuel Anongeba Anaba; Anita Anima Daniels; Anita Asiwome Adzo Baku; James Akazili (BMC, 2024)
Abstract Background Antenatal care services play a crucial role in promoting positive pregnancy outcomes by facilitating the early identification of pregnancy risk factors and early diagnosis of pregnancy-related complications. This study aimed to assess the frequency and timing of ANC attendance of mothers in Ghana as well as determine the predictors of early ANC attendance. Methods The data for this study was extracted from the 2017 Ghana Maternal Health Survey (GMHS). The study population was women aged 15-49 years with a live birth or stillbirth in the 5 years preceding the survey. Data was analysed using STATA/SE version 17, using descriptive statistics and multiple binary logistic regression analysis. Results It was found that 44.4% of the women obtained eight (8) + ANC visits. A majority of the women (66%) initiated ANC visits in the first trimester of pregnancy. Early ANC visit was significantly associated with age of the respondent, education, wealth index, religion, region and reason for first ANC visit. For instance, women between the ages of 25-29 years (aOR = 1.75, 95% CI: 1.31-2.33) had increased odds of early ANC visit compared to those aged 15-19 years. Women with higher education (aOR = 1.83, 95% CI: 1.27-2.64) were about twice as likely to initiate early ANC visits compared to those with no education. Also, women in the highest wealth index (aOR = 2.43, 95% CI: 1.83-3.23) were two times more likely to initiate early ANC visits compared to those in the lowest wealth index. Conclusion This study has shown that a majority of women in Ghana start their first ANC visit during the first trimester of pregnancy. A considerable proportion of the women failed to meet the WHO's recommendation of having a minimum of eight ANC visits throughout pregnancy. Early ANC visit was determined by socio-demographic factors. Going forward, it should be a priority for stakeholders to ensure that ANC services are accessible to all mothers in a timely manner.